COMMUNICATIVE-FUNCTIONAL APPROACH WHEN TEACHING A SINGLE COMPOSITE SENTENCE (Pedagogy of Higher and Secondary Education, 2008)
The article covers on the lingvistic and didactic's basis of communication and functional study of the mononuclear sentences of learning in modem lessons on Ukrainian language.